Penerapan Metode Simpel Moving Average Untuk Memprediksi Persediaan Tiket Kapal Di Pelabuhan Penyeberangan Gorontalo: Stock up on boat tickets at the Gorontalo crossing port - Nuraini Azis; Muis Nanja; Zohrahayaty (Jurnal Ilmiah Ilmu Komputer Banthayo Lo Komputer, 2023)
Transportation is one of the basic needs of society, both by air, land and sea. Sea shipping at the Gorontalo Ferry Port is the main means of advancing the national economy. Many people choose executive boats to travel because they are fast, comfortable and safe. Before traveling, prospective passengers on executive ships must first book tickets with an agent who determines where they will go and when the ship will depart [2]. Tickets are tools/media that are used by certain companies as a direct substitute for gold. Tickets are usually in the form of paper containing certain items that show value. According to the Big Indonesian Dictionary, ticket "means what is considered as a method of payment used by existing means of transportation"[3]. when commuting. At the port several classes are available for purchasing tickets, namely economy, business and VIP/executive classes. When purchasing tickets, counters are often confused when separating which classes sell more. This results in a slow process of inputting data. In this case the researcher will classify tickets based on the class that sold the most so that it can be seen how many classes are obtained and can make it easier for the ticket counter to input data on tickets sold. Prediction (forecasting) is an attempt to predict or estimate something that will happen in the future by utilizing various relevant information at previous times (historical) through a scientific method. Prediction methods can be carried out qualitatively through expert opinions or quantitatively by calculating mathematically. One of the quantitative prediction methods is using time series analysis [4]. The Simple Moving Average(SMA) is the simplest moving average and does not use its weights to calculate closing price movements. Although simple, SMA is very effective in determining market trends in terms of forecasting. Based on the data processing used by applying the SMA data method that has been tested into the system, each obtains a mape value for the type of business, obtaining a mape of 1.07% for the type economy by 0.28% and VIP type by 0.22%.